Evaluation of the Effectiveness of Implementing Leadership Functions in Regional Public Organizations - Isgunandar, Isgunandar (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
Leaders must have the courage to take necessary action against members who are less productive or violate the rules, in order to maintain the interests and integrity of the organization. This research aims to evaluate the effectiveness of implementing the main leadership functions at the Sinjai Borong District Office, Sinjai Regency. In an organizational context, leadership factors have an important role in driving and directing goal achievement. The research method used was descriptive qualitative, with data collection through interviews, observation and documentation, involving 5 informants. Data analysis uses three stages, namely data reduction, data presentation, and drawing conclusions. The research results show that the implementation of the main leadership functions is not optimal, especially in the consultation and control functions. The limited time of sub-district leaders who hold concurrent positions outside the office hampers communication with their subordinates. Even though there are several indicators that show effectiveness, there are still several things that need to be improved so that the leadership function can run well and support the achievement of organizational goals.